Ingeniería didáctica para la secuencia s generalizada de Jacobsthal y la (s, t) -secuencia Jacobsthal generalizada: análisis preliminares y a priori - Vieira Alves, Francisco Regis (UNIÓN - REVISTA IBEROAMERICANA DE EDUCACIÓN MATEMÁTICA, 2017)
The present work describes the initial two stages of a classical Didactical Engineering with the theme related to properties of the Generalized Sequence of Jacobsthal and the (s,t)-Generalized Sequence of Jacobsthal. Admittedly, such notions were, recently, introduced in the scientific literature by Anatassov (2011; 2012). However, some combinatorial properties can be identitied and investigated with a computational resource. Finally, two problem situations are described, so that the Theory of Educational Situations - TSD was used in order to indicate possible interactions that must be explored involving the trinomial - teacher - knowledge - students. Finally, the work presents a summary table of the properties verified by mathematical induction and that have not been discussed in the scientific literature until the moment, involving process of numerical extension of the respective indices.